2000
DOI: 10.1021/jf000149u
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Wine Aroma:  Release of Aroma Compounds from Reactions between Cysteine and Carbonyl Compounds in Wine

Abstract: Under conditions close to those of wine, that is, low pH, aqueous medium, and low temperatures, this work examines the role of carbonyl (acetoin and acetol) and dicarbonyl (glyoxal, methylglyoxal, diacetyl, and pentane-2,3-dione) compounds associated with cysteine in the formation of odorous products. In particular, thiazole, 4-methylthiazole, 2-acetylthiazole, and trimethyloxazole and two sulfur and oxygenated heterocyclic compounds, 2-furanmethanethiol and thiophene-2-thiol, are examined. For thiophene-2-thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 12 publications
2
79
1
1
Order By: Relevance
“…So it is generally assumed that the odorants with higher OAVs contribute in a stronger manner to the overall aroma (Callejon et al 2008). The odor threshold has been previously reported in related literatures (Burdock 2004;Callejon et al 2008;Marchand et al 2000;Peinado et al 2004;Piccino et al 2013;Taylor et al 2013;Vilanova and Martínez 2007). Compounds in the Table 6 are ranked according to the maximum OAV reached in the eight SAV samples.…”
Section: Oav Calculation and Aroma Wheelmentioning
confidence: 88%
See 1 more Smart Citation
“…So it is generally assumed that the odorants with higher OAVs contribute in a stronger manner to the overall aroma (Callejon et al 2008). The odor threshold has been previously reported in related literatures (Burdock 2004;Callejon et al 2008;Marchand et al 2000;Peinado et al 2004;Piccino et al 2013;Taylor et al 2013;Vilanova and Martínez 2007). Compounds in the Table 6 are ranked according to the maximum OAV reached in the eight SAV samples.…”
Section: Oav Calculation and Aroma Wheelmentioning
confidence: 88%
“…Comparing aroma wheel of SAV to sensory analysis of Sherry vinegar (Callejon et al 2008), we found roasty was a unique flavor for SAV. This preliminary comparison between aroma wheel b Odor activity value defined as ratio between odor concentration and odor threshold c Each compound was attributed to 1 or more classes of the following 6 classes of sensory descriptors: (1), floral, (2), roasty, (3), nutty, (4), fatty, (5), fruity, (6), woody d Burdock (2004) e Callejon et al (2008) f Taylor et al (2013) g Marchand et al (2000) h Piccino et al (2013) i Vilanova and Martínez (2007) * The highest odor activity values of the aroma compounds among the eight Shanxi aged vinegar samples and sensory analysis demonstrated a previous viewpoint: aroma wheel could be a replacement when a sensory analysis is not available or affordable (Capone et al 2013). Among these SAV samples, TB-3-Z and S-3-D presented relatively high scores on most sensory descriptors.…”
Section: Oav Calculation and Aroma Wheelmentioning
confidence: 99%
“…50 However, some studies show that formation of methional can be induced without a thermal process as found in the present study. 51,52 Some dicarbonyl compounds occurring in wine, diacetyl, glyoxal or 2,3-pentanedione, can induce the Strecker reaction of amino acids. Methional could be formed from Strecker degradation of methionine induced by dicarbonyl compounds occurring during fatty acid oxidation.…”
Section: Olfactometry Analysismentioning
confidence: 99%
“…They are very odorous and could be involved in the bouquet of wine. 7 In addition, another aspect of our research relates to the metabolism of amino acids with lactic acid bacteria, whose products contribute to the fermentation aroma of wines. This metabolism is known in yeast and leads to the formation of higher alcohols, 8 methionol 9 and other compounds.…”
Section: Introductionmentioning
confidence: 99%